UMKM Kreatif Karangbahagia Menuju Pasar Digital - Syuhada, Wira; Maha Putra; Ahmad Turmudi Zy (Publikasi Inspirasi Indonesia, 2024)
Micro, Small and Medium Enterprises (MSMEs) in the creative industry sector have great potential in driving economic growth. However, the main challenge faced by MSMEs is limited market access, especially in the current digital economy era. The development of information technology and e-commerce platforms opens new opportunities for MSMEs to expand their marketing reach and increase competitiveness. This research aims to design a human resource development program for creative industry MSMEs in Cikarang Baru in effectively utilizing e-commerce platforms. The research methodology used is a mixed method approach with data collection techniques through surveys, in-depth interviews, and literature studies. Surveys are conducted to identify the profiles, challenges, and opportunities of creative industry MSMEs in Cikarang Baru. In-depth interviews are conducted to explore more information about the constraints and obstacles in utilizing e-commerce platforms as well as the need for human resource development. The research results show that most MSMEs have not optimally utilized e-commerce platforms due to limited knowledge and skills of human resources in managing online sales. The proposed development program includes training, assistance, and capacity building for human resources to operate and manage sales through e-commerce effectively. The development materials cover digital marketing strategies, product and content optimization, online store management, and customer service. With the improvement of human resource skills through this program, it is hoped that creative industry MSMEs in Cikarang Baru can increase market access, expand their marketing reach, and improve competitiveness in the digital economy era